Climate‐Smart Fertilizers in 4R Nutrient Stewardship. Issue 3 (15th April 2022) - Bruulsema, Tom
Abstract : Climate‐smart fertilizers will play an increasingly important role. They fit well into the 4R Nutrient Stewardship concept, which provides an excellent framework for recognizing and rewarding the farmers that adopt their use. Programs, protocols, and policies aimed at reducing the carbon footprint of agriculture need to recognize climate‐smart fertilizer use in a 4R framework. Earn 0.5 CEUs in Nutrient Management by reading this article and taking the quiz at https://web.sciencesocieties.org/Learning‐Center/Courses .